The manager's pocket guide to motivating employees - Doyle, Shawn (Managers Pocket Guide Series., 2005)
Hundreds of reports and statistics prove that a motivating workplace is essential to the success of an organization. This practical guide concisely outlines the steps to creating and maintaining a fun, energized, and highly motivating work environment where employees want to work - and stay. The author believes a smart manager can get 60% of workers to work harder. If a staggering increase in your productivity sounds good, 'The Manager's Pocket Guide to Motivating Employees' is for you. The book inspires managers to accept their responsibility to foster motivation in the workplace. And it makes what they need to do to fulfill their important role simple and understandable. You'll discover proven tips for creating an environment which fosters motivation, including how to: Hire motivated people; Convey the goals of your organization and how employees fit into the big picture; Generate enthusiasm throughout your staff; Set expectations and provide opportunities for growth; Guide and direct employees so they know where they are headed; Understand what really motivates people; Reward and recognize employees for their efforts; Relieve pressure and find balance. It doesn't matter whether you are motivating a lackluster existing team or a new team. This guide - along with the action plans, tools, and worksheets included - will help you take immediate action and make a powerful and lasting impact.